Bioinformatics Analysis of Actin Molecules: Why Quantity Does Not Translate Into Quality? - Glyakina, Anna V.; Galzitskaya, Oxana V. (Frontiers in Genetics, 2020)
The time has come to revise all the available data and find distinctive characteristics of actin, what makes it such important molecule of a cell. Presented double-helix organization of filamentous actin cannot explain the strong polymorphism of actin fibrils. In this work, we performed a bioinformatics analysis of the set of 296 amino acid sequences of actin from representatives of various classes of Chordate type. Based on the results of the analysis, the degree of conservativeness of the primary structure of this protein among representatives of Chordate type was determined. In addition, 155 rabbit actin structures obtained by X-ray diffraction analysis and electron microscopy over the past thirty years were analyzed. From the pairwise alignments and the calculation of the root mean square deviations for these structures, it follows that they are very similar to each other without correlation with the structure resolution and method of reconstruction: the root mean square deviations for 11781 pairs did not exceed 3 angstroms. It turned out that in rabbit actin most of the charged amino acid residues are located inside the protein, which is not typical for protein structure. We found that two exon regions out of six correspond to the structural subdomains. It is necessary to use new approaches and new technique to validate actin structure organization.